Time-dependent and time-integrated angular analysis of B -> phi K-S(0)pi(0) and phi K-+/-pi(-/+) - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
We perform a time-dependent and time-integrated angular analysis of the decays B0→φK*(892)0, φK2*(1430)0, and φ(Kπ)0*0 with the final sample of about 465×106 BB̄ pairs recorded with the BABAR detector. Twenty-four parameters are investigated, including the branching fractions, CP-violation parameters, and parameters sensitive to final-state interactions. We use the dependence on the Kπ invariant mass of the interference between the scalar and vector or tensor components to resolve discrete ambiguities of the strong and weak phases. We use the time evolution of the B→φKS0π0 channel to extract the CP-violation phase difference Δ 00=0.28±0.42±0.04 between the B and B̄ decay amplitudes. When the B→φK±π channel is included, the fractions of longitudinal polarization fL of the vector-vector and vector-tensor decay modes are measured to be 0.494±0.034±0.013 and 0.901-0.058+0.046±0.037, respectively. This polarization pattern requires the presence of a positive-helicity amplitude in the vector-vector decay from a currently unknown source. © 2008 The American Physical Society.